THEORETICAL BASICS FOR DETERMINING INDICATORS OF SUSTAINABLE ECONOMIC DEVELOPMENT OF THE ENTERPRISE - HRYNCHUTSKYI, Valerii; DAVYDENKO, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article considers the theoretical aspects of determining indicators of sustainable development of an enterprise. Special attention is paid to determining the goals of sustainable development in the context of globalization in order to achieve the goals of the UN Global Compact. Indicators of sustainable development are important for reflecting social, economic and environmental parameters in a single complex, and therefore it was important to group them into groups of social indicators (fighting poverty, increasing the level of education, demographic dynamics, protecting people’s health, developing culture, etc.), economic indicators (economic development, changing consumption characteristics, financial resources and mechanisms, cooperation and creating economic potential, etc.) and a group of environmental indicators (environmental preservation, an integrated approach to planning and rational use of natural resources, promoting sustainable agriculture, measures to preserve forests, environmentally safe use of biotechnology, etc.). Special attention is paid to indicators of corporate social responsibility, an important component of sustainable development goals. The article pays significant attention to the enterprises of the agro-industrial complex, since they most fully cover the scope of all the sustainable development goals proposed in the Global Compact, which take into account the development prospects of future generations. The principle of the circular economy, which is gaining popularity in Western economic science, is analyzed. The essence of this economic business model, which is based on minimizing the consumption of limited resources by replacing the concept of "end-of-life cycle" and focusing on the design of materials, products and systems for sustainable development